2023
DOI: 10.4258/hir.2023.29.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nomophobia in University Students: A Systematic Review and Meta-Analysis

Abstract: Objectives: The aim of this study was to assess the prevalence of nomophobia in university students.Methods: A systematic search was conducted of the following databases: Web of Science/ Core Collection, Scopus, PubMed, Embase, and Ovid/ MEDLINE until March 2021. Cross-sectional studies reporting the prevalence of nomophobia in undergraduate or postgraduate university students that assessed nomophobia with the 20-item Nomophobia Questionnaire (NMP-Q) tool were included. Study selection, data extraction, and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…The prevalence nomophobia among university students globally is 100%. 24 Jilisha et al conducted a study in 2019 among Indian undergraduate students and reported that around 98% of undergraduate students experienced nomophobia, with the majority experiencing moderate nomophobia. 25 Additionally, Qutishat et al reported that out of 740 university students in Oman, 99% experienced nomophobia, with 65% experiencing moderate nomophobia.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence nomophobia among university students globally is 100%. 24 Jilisha et al conducted a study in 2019 among Indian undergraduate students and reported that around 98% of undergraduate students experienced nomophobia, with the majority experiencing moderate nomophobia. 25 Additionally, Qutishat et al reported that out of 740 university students in Oman, 99% experienced nomophobia, with 65% experiencing moderate nomophobia.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to the prevalence rates reported in other countries [ 28 ]. A recent systematic review also showed a high prevalence of mild to moderate nomophobia [ 15 ]. A study in Lebanon showed that 1089 (48.3 %) participants had moderate nomophobia, while 349 (15.5 %) had severe nomophobia [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 2023 systematic review summarising 23 papers from 8 countries with approximately 11,300 participants showed that the prevalence of mild, moderate, and severe nomophobia was approximately 24 %, 56 % and 17 %, respectively [ 15 ]. The highest prevalence occurred in the university students population (97.38 %), among other groups, including the general adults, community adolescents and high school student [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, nomophobia (no mobile phone phobia) is considered a modern age-specific anxiety for not being able to communicate, for losing connectedness, for not being able to access information, and for giving up convenience [ 1 ]. The literature is not consistent as regards the wording and the underlying theoretical psychological concepts, in that some are talking about nomophobia [ 1 , 23 , 24 , 25 , 26 , 27 , 28 ], while some claim that excessive smart phone use is considered a smart phone addiction [ 5 , 9 , 10 , 12 , 29 , 30 ] or problematic or excessive smart phone use [ 6 , 11 , 31 , 32 ]. Further, to make the point in the case, nomophobia and excessive smart phone use were associated with higher scores for emotional loneliness and insomnia among a sample of 773 students (mean age: 25.95 years; 59.6% females) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%